COMPUTATIONAL STUDY OF ELECTRON-WITHDRAWING AND DONATING GROUPS EFFECTS ON STRUCTURE AND ELECTRONIC PROPERTIES OF THE 2-(2-METHYLPHENYL)-,4-,5-DIPHENYL-1H-IMIDAZOLE COMPOUND (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the current study, the 2-(2-methylphenyl)-,4-,5-diphenyl-1H-imidazole based (donor (OH) and accepter (NO2) groups) are examined in order to determine the impact of various substituents on the optical and structural properties using density functional theory (DFT) with a global hybrid functional (B3LYP) and 6-311G(d,p) as a basis set. The geometry optimization of 2-(methylphenyl)-,4-,5-diphenyl-1H-imidazole with (donor (OH) and accepter (NO2) groups substitutes in ortho, meta, and para positions have been calculated in the gas phase. It was observed that the two substituted groups exhibited a minimal potential energy distribution (PED) for molecules in the para position. It is observed that the incorporation of an electron withdrawing group (NO2) at the para position and an electron donating group (OH) at the para positions of 2-(2-methylphenyl)-,4-,5-diphenyl-1H-imidazole system resulted in a greater shift towards the blue end of the absorption spectrum. The TD-DFT technique was used to forecast the UV-Vis spectral parameters, including the maximum wavelength, energy, and oscillator strength, of three compounds. The molecule containing a para-positioned NO2 group demonstrated the longest absorption wavelength at λ= 395.13 nm. The HOMO-LUMO energy gaps, global reactivity descriptors and Molecular electrostatic potential surfaces (MEPS) are computed to examine how various substituents impact the structural and optical characteristics of 2-(2-methylphenyl)-,4-,5-diphenyl-1H-imidazole.